Realidades expandidas: Influências da tecnologia no transe religioso - estudo de caso sobre ayahuasca - Moraes, Welliton Rogério Barros (2014)
This dissertation aims to establish correlations between virtuality technology, promoted by computer systems, and the symbolic universe, created by religious affiliation in which the phenomenon of trance exerts primary function. The prerogative postulated for this work is that the expansion and multiplication of realities arising from the intensification of the current use of technology gives the individual communication skills beyond their biological capacity, which in parallel pathways dialogues with religious experiences that involve contacts with extraordinary universes. This argument is unsubstantiated by theorists who have studied the subject and supported by individuals who make religious use of ayahuasca for at least five years, who were subject of case study in this research